PAST THE GLORIOUS AGE: OLD TESTAMENT SCHOLARSHIP IN SOUTH AFRICA—ARE WE MOVING ANYWHERE CLOSE TO BLACKENING OLD TESTAMENT SCHOLARSHIP? - Ramantswana, Hulisani (Scriptura, 2020)
Old Testament scholarship in South Africa has deepened, broadened, and evolved over the years; and various trails can be traced within it. The article interrogates whether Old Testament scholarship has passed the glorious age. The following issues are explored: First, the retirement of scholars in recent years as a signal of the coming to an end of the second-generation of Old Testament scholars in South Africa; second, the developments in black Old Testament scholarship as a trail which developed alongside white Old Testament scholarship; and third, the prospects of Old Testament scholarship from a decolonial perspective. This article argues that the future of Old Testament Scholarship in (South) Africa is in a blackening, that is, a redress process through broadening of the scholarship to reflect the continent in which it has to thrive.